Hamba yang Setia: Diskursus Matius 24:45-51 Sebagai Landasan Pelayanan - Yulianus Bani; Jusni Situmorang; Suhendra suhendra (JURNAL LUXNOS, 2026)
A servant of God understands his own identity before God and others. Understanding identity reflects the true meaning of a faithful servant. Faithfulness is a reflection of God's faithful nature. A slave does not do his own will, but submits to his master. The servant of God often does his own will without following what is desired by God. This is what Matthew 24:45-51 says about the importance of being a faithful servant. This study was conducted to understand the faithful servant discourse of Matthew 24: 45-51 as the foundation of today's Ministry. The writing of this article uses desdriptif-analysis method. Researchers use sources such as books, articles and interviews as material to determine the results of research. The results showed that not all Christians understand about the faithful servant based on Matthew 24: 45-51, and do not have a biblical basis of Service. The discourse of Matthew 24: 45-51 includes doing the will of his master with obedience, faithful, careful and careful (VV. 45), doing his master's work creatively (VV.46), waiting for the coming of his Master by doing a faithful duty (VV. 46).